PESAN AL-QUR’AN TENTANG DAKWAH MODERAT - Baidowi, Ahmad; Ma'rufah, Yuni (UIN Sunan Kalijaga Yogyakarta, 2021)
History shows that the success of Islamic da'wa is not through the ways of violence. Instead, Islam has succeeded in expanding to the communities in most places because it has been preached moderately so that the communities can accept Islam more easily. Moderate and non-violent attitude in conveying da'wa is not only taught by Al-Qur'an or exemplified by Prophet Muhammad SAW, but also acted by the preachers of Islam within the communities. These concepts of non-violence have been successfully applied in various models and approaches for the sake of the people as the subject of Islamic da'wa. This study shows that adaptation is an important point in a moderate approach of da'wa that support the success of the da'wa to societies. In other words, the socio-cultural and psychological approach has been the alternative way in Islamic da’wa in order that Islam becomes more easily accepted by the communities.